Automation of Self-Service Book Borrowing and Return System at POLMAN Bandung Library - Siti Aminah; M. Harry Khomas Saputra; M. Daffa Taufiiqulhakim (Universitas Insan Cendekia Mandiri, 2026)
Technological developments have changed the library landscape, from traditional libraries to smart libraries. Smart libraries are libraries that use information and communication technology to improve efficiency, effectiveness, and user experience. However, the library service system in Polman Bandung has not fully utilized information and communication technology, so the service process is less than optimal. The library service system in Polman Bandung still uses a manual system, making it prone to errors in recording circulation data. The application of the Internet of Things with RFID technology can be one solution to overcome the problem of a library service system that has not been fully digitized and automated. This technology has been used in various industrial sectors, one of which is in library services, from self-checkout to book locating, so that most library services are self-service based. This study aims to develop by designing an automated book borrowing and returning system (Automated Storage & Retrieval System) to improve the efficiency and effectiveness of librarian services by digitizing services from manual to self-service that will become part of a smart library. The VDI 2206 methodology in this study can integrate the mechanical, electrical, and informatics designs needed for a self-service library service system. The results of the self-service system testing include a loan system with a success rate of 84% with an average time of 31.6 seconds per book, while the return system achieved a success rate of 88% with an average time of 47 seconds per book. This system has been proven to be able to speed up the loan process by up to 65% and returns by up to 22% compared to manual methods. These results indicate that the system is able to work stably and efficiently, and can help librarians in reducing workloads and improving the quality of library services through automation and digitalization of the book circulation process.